Electrical characteristics of Si nanocrystal distributed in a narrow layer in the gate oxide near the gate synthesized with very-low-energy ion beams - Ng, Chi Yung (2010)
A nanocrystal Si (nc-Si) distributed in a narrow layer in the gate oxide close to the gate is synthesized with Si ion implantation at 2 keV, and the electrical characteristics of the nc-Si structure are investigated. The onset voltage of the Fowler-Nordheim tunneling of the structure is lower than that of pure SiO2 structure, and it decreases with the nc-Si concentration. The phenomenon is attributed to the reduction of the effective thickness of the tunneling oxide. The application of a positive or negative voltage causes electron or hole trapping in the nc-Si, leading to a positive or negative flatband voltage shift, respectively. A steplike flatband voltage shift as a function of charging voltage is observed, suggesting single electron or hole trapping in the nc-Si at room temperature. On the other hand, the nc-Si structure shows good charge-retention characteristics also.